A double-layer solid electrolyte membrane and preparation method thereof

Through the design of a double-layer solid electrolyte membrane, combining the positive electrode side with high polymer content and the negative electrode side with high inorganic conductive ceramic content, the problem of difficult electrolyte membrane independently forming and narrow electrochemical windows in the prior art is solved, and a solid-state battery with high energy density and oxidation resistance is achieved.

CN119764540APending Publication Date: 2025-04-04SHENZHEN INX ENERGY TECHNOLOGY CO LTD
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202311284733.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-28
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

When the existing organic and inorganic composite solid electrolyte membranes are combined with high content inorganic ceramics and polymers, it is difficult to form films independently on a large area, and the electrochemical window is narrow, which cannot meet the needs of high-voltage positive electrodes.

Method used

The double-layer solid electrolyte membrane design is adopted, with the positive electrode side having a high polymer content layer and the negative electrode side having a high inorganic conductive ceramic content layer (more than 80%). Through this design, film can be formed independently, and has high shear modulus and good processing performance.

Benefits of technology

The effective combination of the negative electrode-side electrolyte layer of high-content ceramic and the positive electrode-side electrolyte layer of low-content ceramic is achieved, ensuring the independent film formation of the electrolyte membrane and the realization of a high-energy density solid-state battery, while improving the oxidation resistance and flexibility of the electrolyte membrane.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119764540A_ABST
    Figure CN119764540A_ABST
Patent Text Reader

Abstract

The present invention discloses a double-layer solid electrolyte membrane and a preparation method thereof. The double-layer solid electrolyte membrane comprises a positive electrode side solid electrolyte layer and a negative electrode side solid electrolyte layer, wherein the positive electrode side solid electrolyte layer comprises a positive electrode side polymer matrix, a lithium salt and a first conductive ceramic powder, and the content of the first conductive ceramic powder is 5% to 20% by mass relative to the total mass of the positive electrode side solid electrolyte layer, and the negative electrode side solid electrolyte layer comprises a negative electrode side polymer matrix, optional succinonitrile, optional lithium salt and a second conductive ceramic powder, wherein the second conductive ceramic powder is a lithium lanthanum zirconium oxide conductive ceramic powder, and the content of the second conductive ceramic powder is 80% to 99% by mass relative to the total mass of the negative electrode side solid electrolyte layer. The double-layer solid electrolyte membrane of the present invention has the advantages of high ionic conductivity and high shear modulus of inorganic conductive ceramics, as well as excellent processing performance of organic polymers.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a double-layer solid electrolyte membrane and a preparation method thereof, and a solid-state lithium metal battery comprising the double-layer solid electrolyte membrane. Background Art

[0002] Due to its high safety and high specific capacity, lithium metal solid-state batteries are considered to be the most promising next-generation energy storage devices. Traditional liquid electrolytes react with lithium metal continuously, which will cause the lithium metal to be continuously consumed to form inactive lithium, thus causing the battery life to decay continuously; or due to uneven deposition, lithium dendrites will pierce the diaphragm, causing the entire battery to fail and bring huge safety risks.

[0003] Solid electrolytes have high mechanical strength and are believed to be able to inhibit the growth of lithium dendrites. Among them, organic-inorganic composite solid electrolytes have good processing properties and are a hot topic in academic and industrial research. However, organic-inorganic composite electrolytes containing a low content of inorganic conductive ceramics (<70% by mass) do not have a high shear modulus and are not sufficient to effectively inhibit the growth of lithium dendrites. However, when the content of ceramic particles is further increased (for example, >80% by mass), due to the decrease in polymer content and limited bonding strength, the composite electrolyte membrane with a high ceramic particle content will become hard and brittle, and cannot be formed independently, which also limits its large-scale production.

[0004] In addition, the electrochemical window of the single polymer organic-inorganic composite electrolyte membrane is narrow, and it cannot be compatible with lithium metal and high-voltage positive electrodes at the same time, which limits its ability to match higher voltage positive electrodes and affects the realization of high energy density lithium metal all-solid-state batteries. Summary of the invention

[0005] The technical problem to be solved by the present invention is that in the current organic-inorganic composite solid electrolyte membrane, a high content of inorganic ceramics and polymers cannot be independently formed into a large-area membrane when composited.

[0006] In order to solve the above technical problems, the present invention provides a novel solid electrolyte membrane, which adopts a double-layer solid electrolyte design, including a positive electrode side solid electrolyte layer with a relatively high polymer content and a negative electrode side solid electrolyte layer with a high inorganic conductive ceramic content (80% by mass or more, preferably >90% by mass), which can be prepared into an independently supported organic-inorganic composite electrolyte membrane. The organic-inorganic composite electrolyte membrane of the present invention has the advantages of high ionic conductivity and high shear modulus of inorganic conductive ceramics, as well as excellent processing performance of organic polymers.

[0007] According to a first aspect of the present invention, there is provided a double-layer solid electrolyte membrane, comprising a positive electrode side solid electrolyte layer and a negative electrode side solid electrolyte layer, wherein the positive electrode side solid electrolyte layer comprises a positive electrode side polymer matrix, a lithium salt and a first conductive ceramic powder, and the content of the first conductive ceramic powder is 5% to 20% by mass relative to the total mass of the positive electrode side solid electrolyte layer, and wherein the negative electrode side solid electrolyte layer comprises a negative electrode side polymer matrix, optional succinonitrile (SN), optional lithium salt and a second conductive ceramic powder, and the second conductive ceramic powder is a lithium lanthanum zirconium oxide conductive ceramic powder, and the content of the second conductive ceramic powder is 80% to 99% by mass relative to the total mass of the negative electrode side solid electrolyte layer.

[0008] In some specific embodiments, the positive electrode side polymer matrix is ​​selected from one or more of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polyacrylonitrile, polypropylene carbonate, preferably polyvinylidene fluoride-hexafluoropropylene copolymer.

[0009] In some specific embodiments, the negative electrode side polymer matrix is ​​one or more selected from polyethylene oxide, polyethylene glycol, polypropylene oxide, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, and polypropylene carbonate, preferably polyethylene oxide.

[0010] In some specific embodiments, the lithium salt is selected from one or more of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium bis(fluorosulfonyl)imide (LiFSI), lithium difluorooxalatoborate (LiDFOB), lithium bis(oxalatoborate) (LiBOB), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), and lithium hexafluorophosphate (LiPF6), preferably lithium bis(trifluoromethanesulfonyl)imide (LiTFSI).

[0011] In some specific embodiments, the first conductive ceramic powder is selected from one or more of lithium lanthanum titanium oxide (LLTO) powder, lithium lanthanum zirconium oxide (LLZO) powder, lithium lanthanum zirconium tantalum oxide (LLZTO) powder, and lithium aluminum titanium phosphide (LATP) powder LATP, preferably lithium lanthanum zirconium oxide (LLZO) powder.

[0012] In some specific embodiments, relative to the total mass of the positive electrode side solid electrolyte layer, the content of the positive electrode side polymer matrix is ​​60 mass % to 85 mass %, and / or the content of the lithium salt is 10 mass % to 35 mass %, and / or the content of the first conductive ceramic powder is 5 mass % to 20 mass %.

[0013] In some specific embodiments, relative to the total mass of the negative electrode side solid electrolyte layer, the content of the negative electrode side polymer matrix is ​​1 mass % to 20 mass %, and / or the content of succinonitrile is 0 mass % to 5 mass %, and / or the content of the lithium salt is 0 mass % to 10 mass %, and / or the content of the second conductive ceramic powder is 80 mass % to 99 mass %.

[0014] In some specific embodiments, the positive electrode side solid electrolyte layer and the negative electrode side solid electrolyte layer may also independently contain a plasticizer. The plasticizer is selected from one or more of polyethylene glycol, ethylene carbonate, butyl benzyl phthalate, and propylene carbonate.

[0015] In some specific embodiments, the particle size of the first conductive ceramic powder is 20 to 1000 nm, preferably 300 nm.

[0016] In some specific embodiments, the particle size of the second conductive ceramic powder is 20 to 1000 nm, preferably 300 nm.

[0017] In some specific embodiments, the thickness of the positive electrode side solid electrolyte layer is 5 μm-20 μm, and the thickness of the negative electrode side solid electrolyte layer is 5 μm-20 μm.

[0018] A second aspect of the present invention provides a method for preparing a double-layer solid electrolyte membrane, the preparation method comprising the following steps:

[0019] (1) preparing a positive electrode side solid electrolyte slurry, coating the prepared positive electrode side solid electrolyte slurry on a release film by scraping and drying to form a positive electrode side solid electrolyte layer;

[0020] (2) preparing a negative electrode side solid electrolyte slurry, applying the prepared negative electrode side solid electrolyte slurry on the positive electrode side solid electrolyte layer by scraping and drying to form a negative electrode side solid electrolyte layer and then forming a double-layer solid electrolyte membrane;

[0021] (3) peeling the double-layer solid electrolyte membrane from the release film and subjecting it to a pressure treatment,

[0022] The positive electrode side solid electrolyte slurry comprises a positive electrode side polymer matrix, a lithium salt and a first conductive ceramic powder, and the content of the first conductive ceramic powder is 5 mass % to 20 mass % relative to the total dry weight of the positive electrode side solid electrolyte slurry, and

[0023] Among them, the solid electrolyte slurry on the negative electrode side comprises a negative electrode side polymer matrix, optional succinonitrile, optional lithium salt and a second conductive ceramic powder, the second conductive ceramic powder is lithium lanthanum zirconium oxide conductive ceramic powder, and the content of the second conductive ceramic powder is 80 mass% to 99 mass% relative to the total dry basis mass of the solid electrolyte slurry on the negative electrode side.

[0024] In some specific embodiments, the positive electrode side polymer matrix is ​​one or more selected from polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polyacrylonitrile, polypropylene carbonate, preferably polyvinylidene fluoride-hexafluoropropylene copolymer.

[0025] In some specific embodiments, the negative electrode side polymer matrix is ​​one or more selected from polyethylene oxide, polyethylene glycol, polypropylene oxide, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, and polypropylene carbonate, preferably polyethylene oxide.

[0026] In some specific embodiments, the lithium salt is selected from one or more of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium bis(fluorosulfonyl)imide (LiFSI), lithium difluorooxalatoborate (LiDFOB), lithium bis(oxalatoborate) (LiBOB), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), and lithium hexafluorophosphate (LiPF6), preferably lithium bis(trifluoromethanesulfonyl)imide (LiTFSI).

[0027] In some specific embodiments, the first conductive ceramic powder is selected from one or more of lithium lanthanum titanium oxide (LLTO) powder, lithium lanthanum zirconium oxide (LLZO) powder, lithium lanthanum zirconium tantalum oxide (LLZTO) powder, and lithium aluminum titanium phosphide (LATP) powder, preferably lithium lanthanum zirconium oxide (LLZO) powder.

[0028] In some specific embodiments, relative to the total dry mass of the positive electrode side solid electrolyte slurry, the content of the positive electrode side polymer matrix is ​​60 mass % to 85 mass %, and / or the content of the lithium salt is 10 mass % to 35 mass %, and / or the content of the first conductive ceramic powder is 5 mass % to 20 mass %.

[0029] In some specific embodiments, relative to the total dry mass of the solid electrolyte slurry on the negative electrode side, the content of the negative electrode side polymer matrix is ​​1 mass % to 20 mass %, and / or the content of the succinonitrile is 0 mass % to 5 mass %, and / or the content of the lithium salt is 0 mass % to 10 mass %, and / or the content of the second conductive ceramic powder is 80 mass % to 99 mass %.

[0030] In some specific embodiments, the viscosity of the positive electrode side solid electrolyte slurry and the negative electrode side solid electrolyte slurry is independently 180-250 mPa·s.

[0031] In some specific embodiments, the scraping thickness of the solid electrolyte slurry on the positive electrode side is 30-100 μm, and the thickness of the solid electrolyte layer on the positive electrode side after drying is 5 μm-20 μm, and the scraping thickness of the solid electrolyte slurry on the negative electrode side is 30-100 μm, and the thickness of the solid electrolyte layer on the negative electrode side after drying is 5 μm-20 μm.

[0032] The third aspect of the present invention provides the use of the double-layer solid electrolyte membrane of the first aspect of the present invention or the double-layer solid electrolyte membrane obtained by the preparation method of the second aspect of the present invention in a solid-state lithium metal battery.

[0033] The fourth aspect of the present invention provides a solid-state lithium metal battery, which comprises the double-layer solid electrolyte membrane of the first aspect of the present invention or the double-layer solid electrolyte membrane obtained by the preparation method of the second aspect of the present invention. Preferably, the solid-state lithium metal battery is a semi-solid-state battery.

[0034] In summary, the present invention provides an organic-inorganic composite solid electrolyte membrane, which adopts a double-layer solid electrolyte design. In the polymer organic-inorganic composite electrolyte layer, the first layer is a high-pressure polymer organic-inorganic composite electrolyte layer with a low content of ceramic powder on the positive electrode side, and the second layer is a high-content ceramic powder on the negative electrode side (80% by mass or more, preferably >90% by mass). The first layer of high-voltage polymer can match the high-voltage positive electrode and has a very good film-forming effect. The second layer of electrolyte uses the first layer (positive electrode side) electrolyte membrane as a substrate, and is coated with an organic-inorganic composite electrolyte with a high content of conductive ceramic powder (solid electrolyte on the negative electrode side). The organic-inorganic composite electrolyte of the present invention has a relatively high shear modulus and can effectively inhibit the growth of lithium dendrites.

[0035] According to the double-layer structure solid electrolyte membrane design of the present invention, the high-content LLZO solid electrolyte on the negative electrode side can be closely attached to the positive electrode side solid electrolyte. This double-layer electrolyte design ensures that the high-LLZO ceramic content of the negative electrode side solid electrolyte can be attached to the positive electrode side solid electrolyte with low LLZO ceramic content on the positive electrode side to form a film independently. Therefore, this double-layer structure design can not only produce solid electrolyte membranes on a large scale by roll-to-roll, but also the electrolyte membrane has higher oxidation resistance, can match high-voltage positive electrode materials, and realize solid-state batteries with higher energy density. At the same time, the double-layer structure solid electrolyte membrane according to this embodiment can be bent and folded, and has excellent flexibility. In addition, the electrochemical window of the double-layer structure solid electrolyte membrane according to the present invention is wider than that of the single-layer solid electrolyte membrane. On the basis of the above, the present invention also provides a method for preparing an organic-inorganic composite solid electrolyte membrane, which uses a traditional scraping film-forming process, does not add additional equipment, has low cost, simple method, controllable thickness, is suitable for large-scale production, and can also obtain the above technical effects. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 A schematic structural diagram of an embodiment of a double-layer solid electrolyte membrane of the present invention is shown.

[0037] Figure 2 An optical photograph showing a double-layer solid electrolyte membrane according to an embodiment of the present invention.

[0038] Figure 3 An optical photograph of a single-layer solid electrolyte membrane according to a comparative example of the present invention is shown.

[0039] Figure 4 The test results of the electrochemical windows of the double-layer solid electrolyte membrane according to the embodiment of the present invention and the single-layer solid electrolyte membrane according to the comparative example are shown. DETAILED DESCRIPTION

[0040] The present invention will be further described below by specific embodiments. Unless otherwise specified, the terms used herein have the same meaning as those of ordinary skill in the art generally understand. The numerical limits or ranges stated herein include endpoints, specifically all values ​​and subranges within the numerical limits or ranges.

[0041] The first aspect of the present invention provides a composite solid electrolyte membrane, such as Figure 1 As shown, the double-layer solid electrolyte membrane includes a positive electrode side solid electrolyte layer 1 and a negative electrode side solid electrolyte layer 2.

[0042] The positive electrode side solid electrolyte layer 1 comprises a positive electrode side polymer matrix, a lithium salt and a first conductive ceramic powder, wherein the content of the first conductive ceramic powder is 5 mass % to 20 mass % relative to the total mass of the positive electrode side solid electrolyte layer 1, and

[0043] Among them, the negative electrode side solid electrolyte layer 2 comprises a negative electrode side polymer matrix, optional succinonitrile, optional lithium salt and a second conductive ceramic powder, the second conductive ceramic powder is lithium lanthanum zirconium oxide conductive ceramic powder, and relative to the total mass of the negative electrode side solid electrolyte layer 2, the content of the second conductive ceramic powder is 80 mass% to 99 mass%.

[0044] In the present invention, the term "optionally" means that the component is selectively included or not included in the composition, that is, according to the specific embodiment, the content of the component may be 0 or may not be 0. Specifically, in the negative electrode side solid electrolyte layer 2 of the present invention, the content of succinonitrile and / or lithium salt may be 0. When the content of succinonitrile and lithium salt is 0, the negative electrode side solid electrolyte layer 2 of the present invention comprises a negative electrode side polymer matrix and a second conductive ceramic powder.

[0045] In the present invention, the positive electrode side polymer matrix includes but is not limited to one or more of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polyacrylonitrile, and polypropylene carbonate, preferably polyvinylidene fluoride-hexafluoropropylene copolymer. Relative to the total mass of the positive electrode side solid electrolyte layer 1, the content of the positive electrode side polymer matrix is ​​60 mass % to 85 mass %, preferably 60 mass % to 80 mass %. The weight average molecular weight of the positive electrode side polymer matrix (for example, polyvinylidene fluoride-hexafluoropropylene copolymer) is 100K-500K, such as 100K, 200K, 300K, 400K, 500K, etc., preferably 400K.

[0046] In the present invention, the negative electrode side polymer matrix includes but is not limited to one or more of polyethylene oxide, polyethylene glycol, polypropylene oxide, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, and polypropylene carbonate, preferably polyethylene oxide. Relative to the total mass of the negative electrode side solid electrolyte layer 2, the content of the negative electrode side polymer matrix is ​​1% to 20% by mass, preferably 1% to 8% by mass. The viscosity-average molecular weight of the negative electrode side polymer matrix (e.g., polyethylene oxide PEO) can be 600K-10000K, such as 600K, 2000K, 4000K, 5000K, 7900K, 10000K, etc., preferably 7900K.

[0047] In the present invention, the lithium salt can be selected from one or more of bis(trifluoromethanesulfonic acid) amide lithium (LiTFSI), bis(fluorosulfonyl) imide lithium (LiFSI), difluorooxalate lithium borate (LiDFOB), bis(oxalate) borate lithium (LiBOB), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), and lithium hexafluorophosphate (LiPF6), preferably bis(trifluoromethanesulfonic acid) amide (LiTFSI). Relative to the total mass of the positive electrode side solid electrolyte layer 1, the content of the lithium salt is 10% to 40% by mass, preferably 15% to 25% by mass. Relative to the total mass of the negative electrode side solid electrolyte layer 2, the content of the lithium salt is 0% to 10% by mass, preferably 0% to 8% by mass, and more preferably 2% to 8% by mass.

[0048] In the present invention, the first conductive ceramic powder can be selected from one or more of lithium lanthanum titanium oxide (LLTO) powder, lithium lanthanum zirconium oxide (LLZO) powder, lithium lanthanum zirconium tantalum oxide (LLZTO) powder, and lithium aluminum titanium phosphide (LATP) powder, preferably lithium lanthanum zirconium oxide (LLZO) powder. Relative to the total mass of the positive electrode side solid electrolyte layer 1, the content of the first conductive ceramic powder is 5% to 20% by mass, for example, 5%, 10%, 15%, 20%, etc., preferably 10% to 15% by mass.

[0049] In the present invention, the content of the second conductive ceramic powder relative to the total mass of the solid electrolyte layer 2 on the negative electrode side is 80 mass% to 99 mass%, for example, it can be 80 mass%, 81 mass%, 82 mass%, 83 mass%, 84 mass%, 85 mass%, 86 mass%, 87 mass%, 88 mass%, 89 mass%, 90 mass%, 91 mass%, 92 mass%, 93 mass%, 94 mass%, 95 mass%, 96 mass%, 97 mass%, 98 mass%, 99 mass%, etc., preferably 85 mass% to 99 mass%, and more preferably 89 mass% to 99 mass%.

[0050] For organic-inorganic composite electrolyte membranes, when the mass ratio of organic ceramic powder reaches 80% by mass or more, it can be considered that a structure of polymer distributed in the ceramic phase ("polymer in ceramic") is formed, in which lithium ions will be conducted along the continuous ceramic powder, so that the electrolyte membrane has higher ionic conductivity and shear modulus.

[0051] In the present invention, the content of succinonitrile is 0% by mass to 5% by mass, preferably 2% by mass to 5% by mass, relative to the total mass of the negative electrode-side solid electrolyte layer.

[0052] In the present invention, the positive electrode side solid electrolyte layer and the negative electrode side solid electrolyte layer may also independently contain a plasticizer. The plasticizer may be selected from one or more of polyethylene glycol, ethylene carbonate, butyl benzyl phthalate, and propylene carbonate PC. Relative to the total mass of the positive electrode side solid electrolyte layer or the negative electrode side solid electrolyte layer, the content of the plasticizer may be, for example, 1% to 20% by mass, preferably 5% to 10% by mass.

[0053] In the present invention, the particle size of the first conductive ceramic powder is 20 to 1000 nm, preferably 300 nm.

[0054] In the present invention, the particle size of the second conductive ceramic powder is 20 to 1000 nm, preferably 300 nm.

[0055] In the present invention, the thickness of the positive electrode side solid electrolyte layer is 5 to 20 μm, and the thickness of the negative electrode side solid electrolyte layer is 5 to 20 μm.

[0056] A second aspect of the present invention provides a method for preparing a double-layer solid electrolyte membrane, the preparation method comprising the following steps:

[0057] (1) preparing a positive electrode side solid electrolyte slurry, coating the prepared positive electrode side solid electrolyte slurry on a release film by scraping and drying to form a positive electrode side solid electrolyte layer;

[0058] (2) preparing a negative electrode side solid electrolyte slurry, applying the prepared negative electrode side solid electrolyte slurry on the positive electrode side solid electrolyte layer by scraping and drying to form a negative electrode side solid electrolyte layer and then forming a double-layer solid electrolyte membrane;

[0059] (3) peeling the double-layer solid electrolyte membrane from the release film and subjecting it to a pressure treatment,

[0060] The positive electrode side solid electrolyte slurry may include a positive electrode side polymer matrix, a lithium salt and a first conductive ceramic powder, and the content of the first conductive ceramic powder is 5 mass % to 20 mass % relative to the total dry mass of the positive electrode side solid electrolyte slurry (i.e., the mass of the slurry without solvent, the same below), and

[0061] Among them, the solid electrolyte slurry on the negative electrode side may include a negative electrode side polymer matrix, optional succinonitrile, optional lithium salt and a second conductive ceramic powder, the second conductive ceramic powder is lithium lanthanum zirconium oxide conductive ceramic powder, and the content of the second conductive ceramic powder is 80 mass % to 99 mass % relative to the total dry basis mass of the solid electrolyte slurry on the negative electrode side.

[0062] In the present invention, relative to the total dry mass of the solid electrolyte slurry on the positive electrode side, the content of the polymer matrix on the positive electrode side can be 60 mass % to 85 mass %, and / or, the content of the lithium salt is 10 mass % to 35 mass %, and / or, the content of the first conductive ceramic powder is 5 mass % to 20 mass %.

[0063] In the present invention, relative to the total dry mass of the solid electrolyte slurry on the negative electrode side, the content of the polymer matrix on the negative electrode side can be 1 mass % to 20 mass %, and / or, the content of succinonitrile is 0 mass % to 5 mass %, and / or, the content of lithium salt is 0 mass % to 10 mass %, and / or, the content of the second conductive ceramic powder is 80 mass % to 99 mass %.

[0064] For example, in step (1), the first layer of the positive electrode side solid electrolyte is first prepared by mixing the positive electrode side polymer matrix and lithium salt, adding a solvent to dissolve the polymer and lithium salt, and then adding the conductive ceramic powder, stirring and dispersing them evenly to form a slurry with a certain viscosity. The stirred and dispersed slurry is scraped on the release film with a scraper, dried naturally for 30 minutes, and then placed in a vacuum drying oven at 80°C for 8 hours.

[0065] In the present invention, the release film may be any release film commonly used for preparing a solid electrolyte membrane, for example, a polyethylene terephthalate (PET) release film.

[0066] In some specific embodiments, the positive electrode side polymer matrix may include one or more of polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP), polyacrylonitrile (PAN), polypropylene carbonate (PPC), preferably polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP). The weight average molecular weight of the positive electrode side polymer matrix (e.g., polyvinylidene fluoride-hexafluoropropylene copolymer) may be 100K-500K, such as 100K, 200K, 300K, 400K, 500K, etc., preferably 400K.

[0067] In some specific embodiments, the lithium salt may include one or more of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium bis(fluorosulfonyl)imide (LiFSI), lithium difluorooxalatoborate (LiDFOB), lithium bis(oxalatoborate) (LiBOB), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), and lithium hexafluorophosphate (LiPF6), preferably (LiTFSI).

[0068] In some specific embodiments, the first conductive ceramic powder may be one or more of lithium lanthanum titanium oxide (LLTO) powder, lithium lanthanum zirconium oxide (LLZO) powder, lithium lanthanum zirconium tantalum oxide (LLZTO) powder, and lithium aluminum titanium phosphide (LATP) powder, preferably LLZO. The particle size of the first conductive ceramic powder may be 20-1000 nm, preferably 300 nm.

[0069] In some specific embodiments, the solvent can be one or more of N,N dimethylformamide (DMF), N-methylpyrrolidone (NMP), acetone, dimethyl sulfoxide (DMSO), preferably DMF. The amount of the solvent can be, for example, 2-15 times the weight of the base polymer, preferably 3-10 times.

[0070] In some specific embodiments, the viscosity of the solid electrolyte slurry on the positive electrode side can be 180-250mPa·s, for example, 185mPa·s, 190mPa·s, 195mPa·s, 200mPa·s, 205mPa·s, 210mPa·s, 215mPa·s, 220mPa·s, 225mPa·s, 230mPa·s, 235mPa·s, 240mPa·s or 245mPa·s, etc.

[0071] In some specific embodiments, the coating thickness of the solid electrolyte slurry on the positive electrode side may be 30-100 μm, and the thickness of the solid electrolyte layer on the positive electrode side after drying may be 5 μm-20 μm.

[0072] For example, in step (2), a solid electrolyte slurry on the negative electrode side is prepared, and the negative electrode side polymer matrix (for example, polyethylene oxide PEO), succinonitrile, lithium salt, and lithium lanthanum zirconium oxide LLZO conductive ceramic powder as the second conductive ceramic powder are uniformly mixed using acetonitrile as a solvent, for example, by ball milling in a ball mill to mix and disperse them uniformly.

[0073] In some specific embodiments, the negative electrode side polymer matrix may include one or more of polyethylene oxide, polyethylene glycol, polypropylene oxide, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, and polypropylene carbonate, preferably polyethylene oxide. The viscosity-average molecular weight of the negative electrode side polymer matrix (e.g., polyethylene oxide PEO) may be 600K-10000K, such as 600K, 2000K, 4000K, 5000K, 7900K, 10000K, etc., preferably 7900K.

[0074] In some specific embodiments, the lithium salt may include one or more of LiTFSI, LiFSI, LiDFOB, LiBOB, LiClO4, LiAsF6, and LiPF6, preferably LiTFSI.

[0075] In some specific embodiments, the particle size of the lithium lanthanum zirconium oxide (LLZO) conductive ceramic powder used as the second conductive ceramic powder may be 20-1000 nm, preferably 300 nm.

[0076] In some specific embodiments, the viscosity of the solid electrolyte slurry on the negative electrode side can be 180-250mPa·s, for example, 185mPa·s, 190mPa·s, 195mPa·s, 200mPa·s, 205mPa·s, 210mPa·s, 215mPa·s, 220mPa·s, 225mPa·s, 230mPa·s, 235mPa·s, 240mPa·s or 245mPa·s, etc.

[0077] Specifically, in step (3), the two electrolytes are composited into a film. The uniformly dispersed negative electrode side electrolyte slurry prepared in step (2) is scraped onto the positive electrode side solid electrolyte layer prepared in step (1). Then, it is placed in a fume hood to dry naturally for 10 min-1 h to volatilize the solvent on the surface, and then placed in a vacuum drying oven at 50-80°C to dry for 5-20 h. The dried organic-inorganic composite electrolyte membrane is torn off from the release film and rolled using a roller press. The thickness after rolling is, for example, 70-90% of the thickness before rolling, preferably 80%.

[0078] The coating thickness of the solid electrolyte slurry on the negative electrode side can be 30-100 μm, and the thickness of the solid electrolyte slurry on the negative electrode side after drying can be 5 μm-20 μm.

[0079] The third aspect of the present invention provides the use of the double-layer solid electrolyte membrane of the first aspect of the present invention or the double-layer solid electrolyte membrane obtained by the preparation method of the second aspect of the present invention in a solid-state lithium metal battery.

[0080] The fourth aspect of the present invention provides a solid-state lithium metal battery, which comprises the double-layer solid electrolyte membrane of the first aspect of the present invention or the double-layer solid electrolyte membrane obtained by the preparation method of the second aspect of the present invention. Preferably, the solid-state lithium metal battery is a semi-solid-state battery. Among them, a semi-solid-state battery refers to a solid-state battery in which the mass of liquid in the battery accounts for 1-10%.

[0081] The present invention is described in detail below by way of examples, which are not intended to limit the present invention. The experimental methods in the following examples are conventional methods unless otherwise specified.

[0082] In the following examples, the weight average molecular weight of the PVDF-HFP used is 400K; the viscosity average molecular weight of PEO is 7900K; and the particle size of the LLZO ceramic powder is 300nm.

[0083] Example:

[0084] Example 1

[0085] This embodiment provides a double-layer solid electrolyte membrane, such as Figure 1 As shown, the double-layer solid electrolyte membrane includes a positive electrode side solid electrolyte layer 1 and a negative electrode side solid electrolyte layer 2.

[0086] The positive electrode side solid electrolyte layer 1 is composed of PVDF-HFP, LiTFSI and LLZO ceramic powder, wherein the mass parts of the above components relative to the total mass of the positive electrode side solid electrolyte layer 1 are: 60 parts of PVDF-HFP, 25 parts of LiTFSI and 15 parts of LLZO ceramic powder.

[0087] The negative electrode side solid electrolyte layer 2 is composed of PEO and LLZO ceramic powder, wherein the mass parts of the above components relative to the total mass of the negative electrode side solid electrolyte layer 2 are: 1 part of PEO and 99 parts of LLZO ceramic powder.

[0088] First, a positive electrode solid electrolyte slurry was prepared according to the following preparation steps (1).

[0089] 60 parts by mass of PVDF-HFP was used as the matrix polymer, mixed with 25 parts by mass of lithium salt LiTFSI, and dissolved in DMF as a solvent, wherein the amount of DMF used was 4 times the mass of PVDF-HFP. After complete dissolution, 15 parts by mass of LLZO ceramic powder was added, stirred and dispersed evenly, and then coated on the PET release film with a scraper to form a film with a thickness of 30 μm. The film was dried naturally in a fume hood for 30 minutes to evaporate the surface solvent, and then placed in a vacuum drying oven at 80°C for 8 hours for use.

[0090] Next, the negative electrode side solid electrolyte slurry was prepared according to the following preparation step (2).

[0091] 1 part of PEO is used as the second layer matrix polymer, mixed with 99 parts of LLZO ceramic powder, and acetonitrile is used as the solvent, wherein the amount of acetonitrile used is 40 times the mass of PEO. The mixed slurry is placed in a high-energy ball mill for ball milling and dispersion.

[0092] Then, a double-layer solid electrolyte membrane was prepared according to the following preparation step (3).

[0093] The uniformly dispersed negative electrode side solid electrolyte slurry prepared in step (2) is scraped onto the positive electrode side solid electrolyte layer prepared in step (1), and the thickness of the slurry scraped is 30 μm. Then, it is placed in a fume hood for natural drying for 30 minutes to volatilize the surface solvent, and then placed in a vacuum drying oven at 60°C for 8 hours. The dried organic-inorganic composite electrolyte membrane is torn off from the PET release film and rolled using a roller press.

[0094] In the double-layer solid electrolyte membrane finally obtained, the thickness of the solid electrolyte layer on the positive electrode side was 10 μm, and the thickness of the solid electrolyte layer on the negative electrode side was 15 μm.

[0095] Example 2

[0096] This embodiment provides a double-layer solid electrolyte membrane, such as Figure 1 As shown, the double-layer solid electrolyte membrane includes a positive electrode side solid electrolyte layer 1 and a negative electrode side solid electrolyte layer 2.

[0097] The positive electrode side solid electrolyte layer 1 is composed of PVDF-HFP, LiTFSI and LLZO ceramic powder, wherein the mass parts of the above components relative to the total mass of the positive electrode side solid electrolyte layer 1 are: 60 parts of PVDF-HFP, 25 parts of LiTFSI and 15 parts of LLZO ceramic powder.

[0098] The negative electrode side solid electrolyte layer 2 is composed of PEO, LiTFSI, succinonitrile and LLZO ceramic powder, wherein the mass parts of the above components relative to the total mass of the negative electrode side solid electrolyte layer 2 are: 6 parts of PEO, 3 parts of LiTFSI, 2 parts of succinonitrile and 89 parts of LLZO ceramic powder.

[0099] First, a positive electrode solid electrolyte slurry was prepared according to the following preparation steps (1).

[0100] 60 parts by mass of PVDF-HFP was used as the matrix polymer, mixed with 25 parts by mass of lithium salt LiTFSI, and dissolved in DMF as a solvent, wherein the amount of DMF used was 4 times the mass of PVDF-HFP. After complete dissolution, 15 parts by mass of LLZO ceramic powder was added, stirred and dispersed evenly, and then coated on the PET release film with a scraper to form a film with a thickness of 30um. The film was dried naturally in a fume hood for 30 minutes to evaporate the surface solvent, and then placed in a vacuum drying oven at 80°C for 8 hours for use.

[0101] Next, the negative electrode side solid electrolyte slurry was prepared according to the following preparation step (2).

[0102] 6 parts of PEO were used as the second layer matrix polymer, mixed with 3 parts of lithium salt LiTFSI, 2 parts of succinonitrile, and 89 parts of LLZO ceramic powder, and acetonitrile was used as the solvent, wherein the amount of acetonitrile used was 40 times the mass of PEO. The mixed slurry was placed in a high-energy ball mill for ball milling dispersion.

[0103] Then, a double-layer solid electrolyte membrane was prepared according to the following preparation step (3).

[0104] The uniformly dispersed negative electrode side solid electrolyte slurry prepared in step (2) is scraped onto the positive electrode side solid electrolyte layer prepared in step (1), and the thickness of the slurry scraped is 30 μm. Then, it is placed in a fume hood for natural drying for 30 minutes to volatilize the surface solvent, and then placed in a vacuum drying oven at 60°C for 8 hours. The dried organic-inorganic composite electrolyte membrane is torn off from the PET release film and rolled using a roller press.

[0105] In the double-layer solid electrolyte membrane finally obtained, the thickness of the solid electrolyte layer on the positive electrode side was 10 μm, and the thickness of the solid electrolyte layer on the negative electrode side was 15 μm.

[0106] Example 3

[0107] This embodiment provides a double-layer solid electrolyte membrane, such as Figure 1 As shown, the double-layer solid electrolyte membrane includes a positive electrode side solid electrolyte layer 1 and a negative electrode side solid electrolyte layer 2.

[0108] The positive electrode side solid electrolyte layer 1 is composed of PVDF-HFP, LiTFSI and LLZO ceramic powder, wherein the mass parts of the above components relative to the total mass of the positive electrode side solid electrolyte layer 1 are: 60 parts of PVDF-HFP, 25 parts of LiTFSI and 15 parts of LLZO ceramic powder.

[0109] The negative electrode side solid electrolyte layer 2 is composed of PEO, LiTFSI, succinonitrile and LLZO ceramic powder, wherein the mass parts of the above components relative to the total mass of the negative electrode side solid electrolyte layer 2 are: 10 parts of PEO, 8 parts of LiTFSI, 2 parts of succinonitrile and 80 parts of LLZO ceramic powder.

[0110] First, a positive electrode solid electrolyte slurry was prepared according to the following preparation steps (1).

[0111] 60 parts by mass of PVDF-HFP was used as the matrix polymer, mixed with 25 parts by mass of lithium salt LiTFSI, and dissolved in DMF as a solvent, wherein the amount of DMF used was 4 times the mass of PVDF-HFP. After complete dissolution, 15 parts by mass of LLZO ceramic powder was added, stirred and dispersed evenly, and then coated on the PET release film with a scraper to form a film with a thickness of 30 μm. The film was dried naturally in a fume hood for 30 minutes to evaporate the surface solvent, and then placed in a vacuum drying oven at 80°C for 8 hours for use.

[0112] Next, the negative electrode side solid electrolyte slurry was prepared according to the following preparation step (2).

[0113] 10 parts of PEO were used as the second layer matrix polymer, mixed with 8 parts of lithium salt LiTFSI, 2 parts of succinonitrile, and 80 parts of LLZO ceramic powder, and acetonitrile was used as the solvent, wherein the amount of acetonitrile was 40 times the mass of PEO. The mixed slurry was placed in a high-energy ball mill for ball milling and dispersion.

[0114] Then, a double-layer solid electrolyte membrane was prepared according to the following preparation step (3).

[0115] The uniformly dispersed negative electrode side solid electrolyte slurry prepared in step (2) is scraped onto the positive electrode side solid electrolyte layer prepared in step (1), and the thickness of the slurry scraped is 30 μm. Then put it into a fume hood to dry naturally for 30 minutes to evaporate the solvent on the surface, and then put it into a vacuum drying oven at 60°C to dry for 8 hours. The dried organic-inorganic composite electrolyte membrane is torn off from the PET release film using a roller press.

[0116] In the double-layer solid electrolyte membrane finally obtained, the thickness of the solid electrolyte layer on the positive electrode side was 10 μm, and the thickness of the solid electrolyte layer on the negative electrode side was 15 μm.

[0117] The following comparative examples are prepared with a single-layer solid electrolyte membrane. Figure 1 The positive electrode side electrolyte layer is not included in the embodiment, and only the negative electrode side electrolyte layer is included.

[0118] Comparative Example 1

[0119] This comparative example provides a single-layer solid electrolyte. Figure 1 The positive electrode side electrolyte layer is not included in the embodiment, and only the negative electrode side electrolyte layer is included.

[0120] 4 parts of PEO are used as the matrix polymer, mixed with 2 parts of lithium salt LiTFSI, 2 parts of succinonitrile, and 92 parts of LLZO ceramic powder, and acetonitrile is used as the solvent, wherein the amount of acetonitrile used is 40 times the mass of PEO. The mixed slurry is placed in a high-energy ball mill for ball milling and dispersion.

[0121] Then, the evenly dispersed slurry was poured onto a PTFE evaporating dish, dried naturally in a fume hood for 30 minutes to evaporate the solvent on the surface, and then placed in a vacuum drying oven at 80°C for 8 hours to obtain a single-layer solid electrolyte membrane with a thickness of 100 μm.

[0122] Comparative Example 2

[0123] This comparative example provides a single-layer solid electrolyte. Figure 1 The positive electrode side electrolyte layer is not included in the embodiment, and only the negative electrode side electrolyte layer is included.

[0124] 10 parts of PEO are used as the matrix polymer, mixed with 8 parts of lithium salt LiTFSI, 2 parts of succinonitrile, and 80 parts of LLZO ceramic powder, and acetonitrile is used as the solvent, wherein the amount of acetonitrile used is 40 times the mass of PEO. The mixed slurry is placed in a high-energy ball mill for ball milling and dispersion.

[0125] Then, the evenly dispersed slurry was poured onto a PTFE evaporating dish, dried naturally in a fume hood for 30 minutes to evaporate the solvent on the surface, and then placed in a vacuum drying oven at 80°C for 8 hours to obtain a single-layer solid electrolyte membrane with a thickness of 100 μm.

[0126] evaluate

[0127] Optical images of the solid electrolyte membranes formed according to the above-mentioned embodiments 1 to 3 and comparative examples 1 to 2 were observed to evaluate the film formation conditions. In addition, the electrochemical windows of the solid electrolyte membranes formed according to the above-mentioned embodiments 1 to 3 and comparative examples 1 to 2 were tested to evaluate the anti-oxidation performance of the electrolyte membranes.

[0128] Figure 2 1, 2, and 3 correspond to the double-layer solid electrolyte membranes of Example 1, Example 2, and Example 3, respectively, and Figure 3 1 and 2 correspond to the single-layer solid electrolyte membranes of Comparative Example 1 and Comparative Example 2, respectively.

[0129] Table 1

[0130]

[0131] pass Figure 2 , Figure 3 From the results in Table 1, we can see that Figure 2 As shown, using the double-layer structure solid electrolyte membrane design according to embodiments 1 to 3 of the present invention, the negative electrode side solid electrolyte with a high LLZO content can fit tightly on the positive electrode side solid electrolyte. This double-layer electrolyte design ensures that the negative electrode side solid electrolyte with a high LLZO ceramic content can be attached to the positive electrode side solid electrolyte with a low LLZO ceramic content to form an independent film. Therefore, this double-layer structure design can not only mass-produce solid electrolyte membranes through roll-to-roll, but also the electrolyte membrane has higher oxidation resistance, can match high-voltage positive electrode materials, and achieve higher energy density solid-state batteries. Moreover, the double-layer structure solid electrolyte membrane according to this embodiment is bendable and foldable, and has excellent flexibility. And from Figure 3 It can be seen that despite the increase in polymer (PEO) content (Comparative Example 2), the LLZO solid electrolyte of this comparative example is too brittle to form a film. Figure 4 It can be seen that the electrochemical window of the double-layer solid electrolyte membrane is wider than that of the single-layer solid electrolyte membrane.

Claims

1. A double-layer solid electrolyte membrane, characterized in that: The double-layer solid electrolyte membrane comprises a positive electrode side solid electrolyte layer and a negative electrode side solid electrolyte layer. The positive electrode side solid electrolyte layer comprises a positive electrode side polymer matrix, a lithium salt and a first conductive ceramic powder, and the content of the first conductive ceramic powder is 5 mass % to 20 mass % relative to the total mass of the positive electrode side solid electrolyte layer, and Among them, the negative electrode side solid electrolyte layer comprises a negative electrode side polymer matrix, optional succinonitrile, optional lithium salt and a second conductive ceramic powder, the second conductive ceramic powder is lithium lanthanum zirconium oxide conductive ceramic powder, and the content of the second conductive ceramic powder is 80 mass % to 99 mass % relative to the total mass of the negative electrode side solid electrolyte layer.

2. The double-layer solid electrolyte membrane according to claim 1, wherein: The positive electrode side polymer matrix is ​​one or more selected from polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polyacrylonitrile, polypropylene carbonate, preferably polyvinylidene fluoride-hexafluoropropylene copolymer.

3. The double-layer solid electrolyte membrane according to claim 1, wherein: The negative electrode side polymer matrix is ​​one or more selected from polyethylene oxide, polyethylene glycol, polypropylene oxide, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, and polypropylene carbonate, preferably polyethylene oxide.

4. The double-layer solid electrolyte membrane according to any one of claims 1 to 3, wherein The lithium salt is selected from one or more of lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium difluorooxalatoborate, lithium bis(oxalatoborate), lithium perchlorate, lithium hexafluoroarsenate, and lithium hexafluorophosphate, preferably lithium bis(trifluoromethanesulfonyl)imide.

5. The double-layer solid electrolyte membrane according to any one of claims 1 to 4, wherein The first conductive ceramic powder is selected from one or more of lithium lanthanum titanium oxide powder, lithium lanthanum zirconium oxide powder, lithium lanthanum zirconium tantalum oxide powder, and lithium aluminum titanium phosphorus powder, preferably lithium lanthanum zirconium oxide powder.

6. The double-layer solid electrolyte membrane according to any one of claims 1 to 5, wherein Relative to the total mass of the positive electrode side solid electrolyte layer, the content of the positive electrode side polymer matrix is ​​60 mass % to 85 mass %, and / or the content of the lithium salt is 10 mass % to 35 mass %, and / or the content of the first conductive ceramic powder is 5 mass % to 20 mass %.

7. The double-layer solid electrolyte membrane according to any one of claims 1 to 6, wherein Relative to the total mass of the solid electrolyte layer on the negative electrode side, the content of the negative electrode side polymer matrix is ​​1 mass % to 20 mass %, and / or the content of succinonitrile is 0 mass % to 5 mass %, and / or the content of the lithium salt is 0 mass % to 10 mass %, and / or the content of the second conductive ceramic powder is 80 mass % to 99 mass %.

8. The double-layer solid electrolyte membrane according to any one of claims 1 to 7, wherein The positive electrode side solid electrolyte layer and the negative electrode side solid electrolyte layer each independently contain a plasticizer, Wherein, the plasticizer is selected from one or more of polyethylene glycol, ethylene carbonate, butyl benzyl phthalate, and propylene carbonate.

9. The double-layer solid electrolyte membrane according to any one of claims 1 to 8, wherein: The particle size of the first conductive ceramic powder is 20 to 1000 nm, preferably 300 nm; and / or the particle size of the second conductive ceramic powder is 20 to 1000 nm, preferably 300 nm; Preferably, the thickness of the positive electrode side solid electrolyte layer is 5 to 20 μm, and the thickness of the negative electrode side solid electrolyte layer is 5 to 20 μm.

10. A method for preparing a double-layer solid electrolyte membrane, characterized in that: The preparation method comprises the following steps: (1) preparing a positive electrode side solid electrolyte slurry, coating the prepared positive electrode side solid electrolyte slurry on a release film by scraping and drying to form a positive electrode side solid electrolyte layer; (2) preparing a negative electrode side solid electrolyte slurry, applying the prepared negative electrode side solid electrolyte slurry on the positive electrode side solid electrolyte layer by scraping and drying to form a negative electrode side solid electrolyte layer and then forming a double-layer solid electrolyte membrane; (3) peeling the double-layer solid electrolyte membrane from the release film and subjecting it to a pressure treatment, The positive electrode side solid electrolyte slurry comprises a positive electrode side polymer matrix, a lithium salt and a first conductive ceramic powder, and the content of the first conductive ceramic powder is 5 mass % to 20 mass % relative to the total dry weight of the positive electrode side solid electrolyte slurry, and Among them, the solid electrolyte slurry on the negative electrode side comprises a negative electrode side polymer matrix, optional succinonitrile, optional lithium salt and a second conductive ceramic powder, the second conductive ceramic powder is lithium lanthanum zirconium oxide conductive ceramic powder, and the content of the second conductive ceramic powder is 80 mass% to 99 mass% relative to the total dry basis mass of the solid electrolyte slurry on the negative electrode side.

11. The preparation method according to claim 10, wherein: The positive electrode side polymer matrix is ​​one or more selected from polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polyacrylonitrile, polypropylene carbonate, preferably polyvinylidene fluoride-hexafluoropropylene copolymer.

12. The preparation method according to claim 11, wherein The negative electrode side polymer matrix is ​​one or more selected from polyethylene oxide, polyethylene glycol, polypropylene oxide, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, and polypropylene carbonate, preferably polyethylene oxide.

13. The preparation method according to any one of claims 10 to 12, wherein The lithium salt is selected from one or more of lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium difluorooxalatoborate, lithium bis(oxalatoborate), lithium perchlorate, lithium hexafluoroarsenate, and lithium hexafluorophosphate, preferably lithium bis(trifluoromethanesulfonyl)imide.

14. The preparation method according to any one of claims 10 to 13, wherein The first conductive ceramic powder is selected from one or more of lithium lanthanum titanium oxide powder, lithium lanthanum zirconium oxide powder, lithium lanthanum zirconium tantalum oxide powder, and lithium aluminum titanium phosphorus powder, preferably lithium lanthanum zirconium oxide powder.

15. The preparation method according to any one of claims 10 to 14, wherein Relative to the total dry mass of the positive electrode side solid electrolyte slurry, the content of the positive electrode side polymer matrix is ​​60 mass % to 85 mass %, and / or the content of the lithium salt is 10 mass % to 35 mass %, and / or the content of the first conductive ceramic powder is 5 mass % to 20 mass %.

16. The preparation method according to any one of claims 10 to 15, wherein Relative to the total dry mass of the solid electrolyte slurry on the negative electrode side, the content of the negative electrode side polymer matrix is ​​1 mass % to 20 mass %, and / or the content of the succinonitrile is 0 mass % to 5 mass %, and / or the content of the lithium salt is 0 mass % to 10 mass %, and / or the content of the second conductive ceramic powder is 80 mass % to 99 mass %.

17. The preparation method according to any one of claims 10 to 16, wherein The viscosity of the positive electrode side solid electrolyte slurry and the negative electrode side solid electrolyte slurry is independently 180-250 mPa·s.

18. The preparation method according to any one of claims 10 to 17, wherein The coating thickness of the positive electrode side solid electrolyte slurry is 30-100 μm, and the thickness of the positive electrode side solid electrolyte layer after drying is 5-20 μm, and The coating thickness of the solid electrolyte slurry on the negative electrode side is 30-100 μm, and the thickness of the solid electrolyte layer on the negative electrode side after drying is 5-20 μm.

19. Use of the double-layer solid electrolyte membrane according to any one of claims 1 to 9 or the double-layer solid electrolyte membrane obtained by the preparation method according to any one of claims 10 to 18 in a solid-state lithium metal battery.

20. A solid-state lithium metal battery, characterized in that: The solid-state lithium metal battery comprises a double-layer solid electrolyte membrane according to any one of claims 1 to 9 or a double-layer solid electrolyte membrane obtained by the preparation method according to any one of claims 10 to 18; Preferably, the solid-state lithium metal battery is a semi-solid-state battery.

Citation Information

Cited By

  • Preparation method of high-ionic-conductivity succinonitrile-based double-layer composite solid electrolyte membrane

    CN120749221A

  • Preparation method of high ionic conductivity succinonitrile-based double-layer composite solid electrolyte membrane

    CN120749221B

  • Double-layer composite polymer solid electrolyte membrane and preparation method thereof

    CN121726516A